Structure, morphology and wettability studies on Langmuir-Schaefer multilayer of poly(vinylidene fluoride)/poly(methyl methacrylate) blends. (November 2017) - Kumar, Chandan; Viswanath, P.
Graphical abstract: Highlights: Multilayer of PVDF/PMMA blends was deposited using Langmuir-Schaefer method. Predominantly present polar β phase at 10% of amorphous PMMA. Porosity of blends increases with fraction of PMMA. Contact angle hysteresis studies showed domination of chemical nature of surface. Abstract: The intermolecular interaction between the polymer chains of different functionality is known to influence the aggregation and molecular chain packing. This way, it is possible to tune the structure, stability and surface quality through the blending of polymers. With this in focus, a systematic studies was carried out to understand structural, morphological and wettability variation in Langmuir-Schaefer multilayer of poly(vinylidene fluoride)/poly(methyl methacrylate) blends. Grazing incidence X-ray diffraction studies on blends showed a Bragg peak around 20.5 ° indicating the predominant presence of polar β phase up to 40% of poly(methyl methacrylate). Its fraction and dielectric environment are estimated using Fourier transform infrared spectroscopy and fluorescence studies, respectively. Morphological features of the blends studied using field emission scanning electron microscope showed a drastic change with increasing fraction of poly(methyl methacrylate). The surface quality and wettability of blends were assessed using contact angle studies. Contact angle and the volume of the sessile drop linearly decrease with time. A relatively faster evaporation of sessile drop was observed for higher fraction of poly(methyl methacrylate) attributed to its hydrophilicity. The evaporation kinetics was found to be largely dependent on the surface quality and chemical nature of poly(vinylidene fluoride)/poly(methyl methacrylate) multilayer.